Sosialisasi Pengaturan Batas Usia Pernikahan Guna Mewujudkan Keluarga Sakinah - Yuniartin, Titin; Handriyanti, Handriyanti; Wimala, Nadya Shofa (Khidmat, 2021)
Academics continue to conduct studies on the age restriction for marriage from different viewpoints. This is because a person's age at marriage is an integral aspect of attaining the objective of marriage, which is to establish a joyful and everlasting family founded on the belief in a single divine entity. The study aimed to analyse the perspective of Muhammadiyah sakinah family on the establishment of age limits for marriage. This study involves normative research utilising secondary legal materials acquired through library research. The acquired data is qualitatively analysed using both a conceptual approach and a statutory method. The findings of this study indicate that the age at which individuals are allowed to marry, as dictated by positive law and Islamic law, differ in their regulations yet share common objectives in promoting marriage. The sakinah family was established by a lawful union. From the Muhammadiyah sakinah family's viewpoint, the selection of a life mate should take into account both liberty and maturity. Maturity for marriage entails more than just biological maturity, since it also encompasses psychological and social preparedness. According to the Marriage Act, this readiness is typically reached at the age of 19.